STUDI HUKUM TANGGUNG JAWAB DROPSHIPPER DAN DISTRIBUTOR PADA TRANSAKSI ONLINE: Responsibility Of Dropshippers With Distributors In Online Business Transactions - Aisyah, Nada (Fakultas Hukum, Universitas Trisakti, 2024)
This paper aims to find out how the legal review of the Dropshipper's responsibility with the distributor. In online-based business transactions, the parties still use the rules in the Civil Code as the rules in making agreements. Another rule used in e-commerce transactions is Law No. 11 of 2008 concerning Information and Electronic Transactions which has been amended by Law No. 19 of 2016 (hereinafter referred to as the ITE Law). In connection with this, this thesis raises three problems, namely first, how is the legal regulation related to agreements in online-based business transactions carried out by dropshippers with distributors, second, how does the existence of a business relationship between dropshippers and distributors affect online-based business transactions, and third, what is the form of legal protection for the division of responsibility between dropshippers and distributors in online-based business transactions